Theoretical study of the single noble metal stabilized on metal oxide clusters catalyze the water‐gas shift reaction. Issue 22 (23rd July 2018) - Xing, Minmin; Guo, Ling; Hao, Zijun
Abstract : The stability of a single noble metal (NM) atom (Ru, Rh, Pd, Ag, Os, Ir, Pt, and Au) supported on various metal oxide clusters (Al3 O5 +, Ce2 O4 +, V2 O6 +, FeO3 −, and Ti3 O7 − ) is higher than that of the widely used metal oxide support surface. The electronic structure analysis shows that the strong hybridization between the d orbital of the NM atom and the oxygen 2p orbital of the ortho position makes the stability of this system significantly enhanced. The higher the center value of the d‐band of Rh‐M x O y ±, the stronger the adsorption of CO on the Rh atom, indicating that the reaction process of Rh‐M x O y ± with CO is easier. By calculating and comparing the rate‐controlling steps of those loaded NMs on the left side of Group VIII of the periodic table, such as Ru, Rh, Os, and Ir, we have determined that the NM‐M x O y ± cluster exhibits a higher catalytic performance for water‐gas shift reaction (WGSR). In particular, RhAl3 O5 + has a lower reaction energy barrier than RhCe2 O4 +, and CeO2 substrate is considered to be the most promising candidate for WGSR, therefore, we speculate that Al3 O5 + cluster is also a promising candidate for this reaction. It is expected that these theoretical results will provide new guidance for designing low‐cost, stable, and efficient heterogeneous single‐atom catalysts for WGSR. Abstract : This article mainly studied the Single Noble Metal Stabilized on Metal Oxide Clusters Catalyze the Water‐Gas Shift Reaction, the main mechanism of the study is the redox mechanism. There are five types of metal oxide clusters studied, they are Al3 O5 +, Ce2 O4 +, V2 O6 +, FeO3 − and Ti3 O7 − . There are eight kinds of single noble metals, namely Ru, Rh, Pd, Ag, Os, Ir, Pt and Au.